Systemic corticosteroids for subcutaneous panniculitis‐like T‐cell lymphoma. (2nd September 2014) - Guenova, E.; Schanz, S.; Hoetzenecker, W.; DeSimone, J.A.; Mehra, T.; Voykov, B.; Urosevic‐Maiwald, M.; Berneburg, M.; Dummer, R.; French, L.E.; Kerl, K.; Kamarashev, J.; et al.
Summary Background Primary cutaneous γ/δ T‐cell lymphoma (PCGD‐TCL) is aggressive and has a poor prognosis. In contrast, subcutaneous panniculitis‐like T‐cell lymphoma (SPTCL) of the α/β T‐cell receptor phenotype is known to follow an indolent course and have a more favourable prognosis. In the past, PCGD‐TCL and SPTCL were often considered to be a manifestation of the same disease, and aggressive systemic polychemotherapy has commonly been the first‐line therapy for both. Given the understanding that SPTCL is a separate and less aggressive entity, clinical data exclusively evaluating the efficacy of conservative treatment in SPTCL are needed. Objectives To assess the overall clinical response to systemic corticosteroids in the treatment of SPTCL. Methods This was a retrospective cross‐sectional study based on a patient data repository from two tertiary care university hospitals in Zürich (Switzerland) and Tübingen (Germany). The repository spanned 13 years. Results In four of the five patients (80%) with SPTCL, treatment with systemic corticosteroids induced a complete remission. Conclusions Systemic corticosteroids may be an excellent first‐line single‐agent therapy for SPTCL.